3' non-coding region sequences in eukaryotic messenger RNA. - Proudfoot, N; Brownlee, G (1976)
The sequence A-A-U-A-A-A is present in six different purified messenger RNA molecules (specifically the alpha-and beta-globulin mRNAs of rabbit and human, the immunoglobulin light chain mRNA of mouse (MOPC 21) and the ovalbumin mRNA of chicken) about 20 residues away from the 3'-terminal poly (A) sequence. In addition, a large selection of the 3' non-coding regions of rabbit and human globulin mRNAs (both the alpha and beta globin mRNAs) are 85% homologous, demonstrating that this region is significantly conserved in evolution.